Eutrophication decreases salt marsh resilience through proliferation of algal mats. (August 2017) - Wasson, Kerstin; Jeppesen, Rikke; Endris, Charlie; Perry, Danielle C.; Woolfolk, Andrea; Beheshti, Kathryn; Rodriguez, Miguel; Eby, Ron; Watson, Elizabeth B.; Rahman, Farzana; Haskins, John; Hughes, Brent B.
Abstract: Globally, many estuaries are affected by nutrient loading from human land uses in the surrounding watersheds. One consequence of increased nutrient levels is proliferation of opportunistic macroalgae. We sought to understand spatial and temporal dynamics of ephemeral macroalgal mats and to examine their effects on salt marsh in a eutrophic estuary in central California. A time series analysis spanning 80 years revealed that algal wrack has increased exponentially in frequency on the salt marsh, and was highly correlated with nutrient concentrations in the estuary, which have increased along with fertilizer use. Analysis of sediment δ 15 N showed a dramatic increase in nutrient loads attributable to agricultural fertilizer over the past 50 years. We monitored 15 salt marsh plots along the bank edge and detected a negative relationship between algal wrack cover and salt marsh cover, flowering, and canopy height. Moreover, algal wrack led to retreat of vegetation from the bank edge, and increased bank erosion. We also experimentally added algal wrack to salt marsh edge plots. Algal addition decreased salt marsh cover, flowering, and canopy height, and increased retreat rate. By integrating time series analyses, isotope data, algal and marsh monitoring and manipulative experiments, we have identified robust linkages between increased anthropogenic nutrient loading, increased algal wrack cover, reduction in marsh resilience and conversion of marsh habitat to mudflat through bank erosion. Decreasing nutrient inputs to eutrophic estuaries is thus essential for conservation and restoration of salt marshes and enhancing their resilience in the face of sea level rise. Highlights: Nitrate concentrations, fertilizer use, and algal wrack have all increased dramatically. Algal wrack accumulates on salt marsh, mostly at the edges of channels. Algal wrack decreases marsh cover, height, and flowering. Moreover, algal wrack leads to vegetation retreat and bank erosion, causing marsh loss. Nutrient-fueled algal wrack thus decreases salt marsh extent and resilience.